Outcomes of the Paul Glaucoma Implant in Refractory Secondary Glaucoma - Khodeiry MM; Hassan AK; Elhusseiny AM; Lee RK; Sayed MS (Clinical Ophthalmology)
Mohamed M Khodeiry,1,2 Amr K Hassan,3 Abdelrahman M Elhusseiny,4 Richard K Lee,2 Mohamed S Sayed5,6 1Department of Ophthalmology and Visual Sciences, University of Louisville, Louisville, KY, USA; 2Department of Ophthalmology, Bascom Palmer Eye Institute University of Miami Miller School of Medicine, Miami, FL, USA; 3Department of Ophthalmology, South Valley University, Qena, Egypt; 4Department of Ophthalmology, Jones Eye Institute, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 5Department of Ophthalmology, Cleveland Clinic Abu Dhabi, Abu Dhabi, United Arab Emirates; 6Department of Ophthalmology, Moorfields Eye Hospital Dubai, Dubai Healthcare City, Dubai, United Arab EmiratesCorrespondence: Mohamed S Sayed, Department of Ophthalmology, Cleveland Clinic Abu Dhabi, Abu Dhabi, United Arab Emirates, Email msayed82@hotmail.comPurpose: To evaluate the efficacy and safety of the Paul Glaucoma Implant (PGI) surgery in patients with secondary glaucomas.Patients and Methods: Retrospective chart review of adult patients with medically recalcitrant secondary glaucoma who underwent PGI implantation at a single tertiary center between August 2022 and June 2023. The primary outcome measure was surgical success. Surgical success was defined as intraocular pressure (IOP) between 6 and 21 mmHg with a ≥ 20% reduction compared to baseline (with or without medications) with no need for implant removal, further glaucoma reoperation, or development of vision-threatening complications at 1 year of follow-up. The secondary outcomes were IOP, glaucoma medication numbers, visual acuity, and surgical complications.Results: Thirty eyes of 30 patients were identified. Nine patients (30%) had neovascular glaucoma, and 9 patients (30%) had silicone-oil-induced glaucoma. At 12 months postoperatively, 28 eyes (93.3%) fulfilled the success criteria. The mean IOP at 12 months was 15.2 ± 4.6 mmHg compared to the mean baseline IOP of 32.6 ± 10 mmHg (p < 0.001). A significant reduction in the mean number of glaucoma medications at 12 months compared to the baseline was observed. The complication rate was 13.3% (4 eyes), with most complications being mild and transient.Conclusion: The PGI demonstrated favorable efficacy and safety profiles in the management of medically uncontrolled secondary glaucomas.Keywords: Paul Glaucoma Implant, secondary glaucoma, intraocular pressure, tube